La solidarietà fondamentale. Liber amicorum Giuseppe Acocella - Vincenzo Rapone (FedOA - Federico II University Press, 2019)
More than a reconstruction of the coordinates of his research, the purpose of this collection is the testimony of a community that approached Giuseppe Acocella, recognizing the prestige of his magisterium. His interests, so diversified, would not have lent themselves to an exegetical reconstruction: rather, we have drawn from the"alive" of his reflections, to the extent that he was able to inspire everyone's research. Moral philosopher, philosopher of the law, philosopher of politics, he was formed starting from the teaching of Capograssi and preferred to direct his reflection on the Lebenswelt, rather than on that formal dimension that would have allowed us a dogmatic reading. Starting from individual inclinations, we wanted to testify to the closeness and significance that Giuseppe Acocella's teaching has played in the search for each one: the topics addressed, which question civil life in its formal and material aspects, reflect the multifaceted tension that only a masterful thinker can inspire.